A biblioteca no contexto da cultura maker: tendências e possibilidades em bibliotecas universitárias - Cabral, Viviane de Holanda (2021)
Makerspaces are spaces defined by collaborative work that provide technologies, tools and resources for the creation of individual and collective projects. However, it is not the equipment that defines the space. The space is evidenced by the strengthening of collective actions. In this sense, the research seeks to interpret how the maker philosophy and the assumptions of maker culture can contribute to university libraries? As for the objectives, this has as general objective: Identify the contributions of maker culture to university libraries, as specific objectives: To analyze the theoretical interlocutions between maker culture and libraries, with emphasis on university libraries; Identify actions, activities and technologies that can be used in maker spaces in university libraries; Identify actions, activities and technologies from the UFC Human Sciences Library that dialogue with the maker philosophy; Therefore, a search was carried out in databases and other formal sources of information, in order to compose a literature review. Thus, it was identified that some libraries in Brazil and in the world have a similar character to the proposal and philosophy of maker spaces. As a methodological strategy, the dialectical perspective was adopted through an exploratory research. From the BCH/UFC, data collection was carried out, through unstructured interviews, on the extension actions developed by the library in the last seven years, via Google Meet and by telephone with the previous and current management of that library. From the contact established with BCH managers and librarians, as well as during informal conversations and discussions, this study fostered a collaborative project to implement a maker space at BCH. The research data show that the extension actions developed by BCH are close to the philosophy of the maker culture, they have an impact, stimulate collaboration and exchange of knowledge between people. It is concluded that the engagement of BCH librarians in the development of extension actions is aligned with the maker culture, especially because it brings at its core collaboration, encouragement of learning, discoveries, co-creation and sharing of resources. Therefore, this research shows that libraries are places that can incorporate aspects of the maker culture and implement these alternative spaces, including in actions that are developed under the aegis of extension, as is already happening in other libraries around the world.